FUNDUS CHANGES IN HYPERTENSION - Jalalova D.Z.; Avazova M.M. (Scholar Express Journals, 2022)
The frequency of eye fundus lesions in patients with essential hypertension (AH), according to various authors, varies from 50 to 95% [1]. This difference is partly due to age and clinical differences in the studied group of patients, but mainly due to the difficulty of interpreting the initial changes in the retinal vessels in hypertension. Internists attach great importance to such changes in the early diagnosis of GB, determining its stage and phase, as well as the effectiveness of the therapy. The most interesting in this regard are the studies of R. Salus. Under the conditions of a well-organized experiment, he showed that the diagnosis of HD, made by him according to the results of ophthalmoscopy, turned out to be correct only in 70% of cases. Errors in diagnosis are associated with significant individual variations in retinal vessels in healthy individuals, and some of the variants (relatively narrow arteries, increased tortuosity of vessels, the “crossover” symptom) can be misinterpreted as hypertensive changes.
Keywords: According to the observations; vessels are not detected; functional; misinterpreted